Pollen Natural Resources for Bees in Slovakia - Chlebo, Róbert; Adamchuk, Leonora (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Studying the pollen resources is a topical issue for both honey bees and people. The aim of our work was pollen natural resources for bees in deferent regions of Slovakia. Pollen grains, bee pollen, bee families and certain species of enthomophile plants served as a biological material. Flowering terms and other information related to the use of protein feed by bees in different regions of Slovakia were obtained after processing the information gained from local beekeepers. The bee pollen was selected several times a month in a set period that was the same for Trenčín, Banská Bystrica, Prešov, Bratislava and Nitra regions. Flower pollen resources were not of the same botanical origin for different regions of Slovakia. Percentage of pollen resources available for bees from different of plants species were established for each region. The definitions were made using pollen analysis of the bee pollen brought by the bees to their homes in the spring and summer periods and also in different decades of months from May to September. Significant resources of flower pollen are characteristic of than Slovak regions of the total: during spring in Trenčín are Robinia spp. – 31%; during spring are Salicaceae – 52% and summer are Helianthus spp. – 64%; during spring in Prestavlky Rosaceae – 42% and summer Brassicaceae – 70%; during spring in Spišský Štiavnik are Salicaceae – 70% and summer: Helianthus spp. – 56%; during spring in Hranivnica are Salicaceae – 60% and summer Epilobium spp. – 90%; during spring in Bratislava are Malus spp. – 35% and summer Helianthus spp. – 46%.